Contributions of birds to the feeding of ticks at host community level: Effects of tick burden, host density and yearly fluctuations - Amalia Rataud; Alex Drouin; Laure Bournez; Benoit Pisanu; Sara Moutailler; Pierre-Yves Henry; Maud Marsot (Ticks and Tick-Borne Diseases)
The eco-epidemiology of tick-borne diseases hinges on the abundance and distribution of hosts that sustain tick populations and the pathogens they carry. Research into the role of bird species in the feeding of Ixodes ricinus ticks, the primary tick species of veterinary and public health importance in Europe, remains scarce. This study endeavors to bridge these knowledge gaps by (i) assessing the density of feeding ticks (DFT) within a bird community to pinpoint species making substantial contributions, and (ii) exploring interannual variations in DFT over an extended timeline. Furthermore, we investigate whether variations in individual tick burden (TB) were more closely associated with the characteristics of bird species or interannual variations affecting the density of questing tick, using interannual TB variation as a surrogate. To fulfill these aims, we conducted a 13-year longitudinal study monitoring I. ricinus ticks feeding on a bird community in a periurban forest in France, covering breeding periods from 2007 to 2019. Within this community, we identified seven principal bird species significantly contributing to I. ricinus tick feeding: the Common Blackbird (Turdus merula), the Song Thrush (Turdus philomelos), the European Robin (Erithacus rubecula), the Dunnock (Prunella modularis), the Eurasian Blackcap (Sylvia atricapilla), the Great Tit (Parus major), and the Common Nightingale (Luscinia megarhynchos). Our results show that the bird community's contribution to tick feeding remained relatively consistent from year-to-year, though certain years displayed higher or lower DFT values related to the average over the study period. Moreover, five out the seven major species accounted for 80 % to 95 % of DFT annually. Consequently, we emphasized the need to broaden the scope of future research on bird contributions to tick population dynamics beyond merely thrushes (Turdidae species), to encompass a more diverse range of species, particularly those common birds that engage in ground foraging activities. Furthermore, variations in individual tick burden were predominantly influenced by the characteristics of bird species rather than by interannual variability in infestation rates. This finding suggests a significant role for species-specific traits in determining tick exposure and susceptibility. In conclusion, our study offers new insights into the medium-term dynamics of tick-bird ecological systems, underscoring the need for future study of tick populations and their interactions with vertebrate hosts to improve our understanding of tick-borne disease circulation.